Does incentive-elicited nucleus accumbens activation differ by substance of abuse? An examination with adolescents. (December 2015) - Karoly, Hollis C.; Bryan, Angela D.; Weiland, Barbara J.; Mayer, Andrew; Dodd, Andrew; Feldstein Ewing, Sarah W.
Highlights: We measure brain activation during anticipation of reward and loss in adolescents. We compare incentive responses in six groups formed based on substance use patterns. No activation differences emerge between the cannabis-only group and the other groups. Tobacco-only users have less reward response than polysubstance and alcohol-only users. Tobacco-only users show decreased reward activation compared to the control group. Abstract: Numerous questions surround the nature of reward processing in the developing adolescent brain, particularly in regard to polysubstance use. We therefore sought to examine incentive-elicited brain activation in the context of three common substances of abuse (cannabis, tobacco, and alcohol). Due to the role of the nucleus accumbens (NAcc) in incentive processing, we compared activation in this region during anticipation of reward and loss using a monetary incentive delay (MID) task. Adolescents (ages 14–18; 66% male) were matched on age, gender, and frequency of use of any common substances within six distinct groups: cannabis-only ( n = 14), tobacco-only ( n = 34), alcohol-only ( n = 12), cannabis + tobacco ( n = 17), cannabis + tobacco + alcohol ( n = 17), and non-using controls ( n = 38). All groups showed comparable behavioral performance on the MID task. The tobacco-only group showed decreased bilateral nucleus accumbens (NAcc) activation during reward anticipation as compared to the alcohol-only group, the control group, and both polysubstance groups. Interestingly, no differences emerged between the cannabis-only group and any of the other groups. Results from this study suggest that youth who tend toward single-substance tobacco use may possess behavioral and/or neurobiological characteristics that differentiate them from both their substance-using and non-substance-using peers.